ASEAN Political Security Community (APSC) on Counter-terrorism: Roles and Obstacles - Faruq Arjuna Hendroy (Jurnal Ilmiah Hubungan Internasional, 2018)
Terrorism issue has been transforming into a worldwide concern. Southeast Asia is undoubtedly currently facing the similar issue. During Afghan war, Southeast Asia might be only known as “the exporters” of foreign militants to Afghanistan’s conflict zone. Going into the 21st century, Southeast Asia has, in turn, become the home base for terrorism itself to grow. Thus, ASEAN, as a regional body which shades Southeast Asia member states, responded to its emergence. ASEAN regarded terrorism a huge threat and paid extremely high attention to it through the release of ASEAN Convention on Counter Terrorism (ACCT). Moreover, ASEAN enhanced its commitment as regional body by composing one pillar of cooperation in security called ASEAN Political Security Community (APSC). APSC helps to drive all ASEAN member states to commit onto ACCT by proceeding to the full ratification by each member state and applying the effective implementation in dealing with the issue. This paper examines APSC’s role  in combating terrorism within region and discusses its obstacles in implementing ACCT.Keywords: ASEAN; ASEAN Political Security Community; Terrorism; ASEAN Convention on Counter-Terrorism; Non-Interference